Ivermectin mass drug administration for onchocerciasis elimination: can it reduce the prevalence of scabies in Ethiopia? - Amsalu, Tsigereda; Enbiale, Wendemagegn; Manaye, Neguse; Ayalew, Ashenafi; Workineh, Addisu; de Vries, Henry; van Griensven, Johan (The Journal of Infection in Developing Countries, 2022)
Introduction: While ivermectin mass drug administration (MDA) has been implemented since long for onchocerciasis elimination, there is doubt whether this would also be effective for scabies control. If effective, this would allow integration of both programs. We compared scabies prevalence in districts implementing ivermectin MDA for the onchocerciasis elimination program and those not implementing the intervention in Amhara region, Ethiopia. Methodology: We conducted a cross-sectional study comparing the scabies prevalence in 14 districts implementing ivermectin MDA for onchocerciasis elimination program between 2013-2018 and in 28 districts without this intervention in Amhara region Ethiopia. We used 2018 scabies survey data to determine scabies prevalence. All individuals screened for scabies during the survey were included. We collected data on risk factors from the districts database and annual reports. Multivariate linear regression analysis was used to account for potential confounding factors. Results: We included data on 4,319,064 subjects across 42 districts. Except the differences in temperature and population density, districts in both groups were comparable. A total of 371,780 scabies cases were detected in the 2018 survey. The median scabies prevalence was 6% (IQR 2.6-11.9) in the intervention districts and 5.2% (1.8-10.4) in the control districts (p-value 0.77). In adjusted analysis, the difference remained statistically non-significant (coefficient 0.37 (95% confidence interval (-0.93-1.67); p-value 0.554). Conclusions: The implementation of ivermectin MDA for onchocerciasis control was not associated with reduced scabies prevalence. Consequently, standard scabies MDA should be deployed for scabies control.